Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality - Rojas, Rommel R.; Fouquet, Antoine; de Carvalho, Vinícius Tadeu; Ron, Santiago; Chaparro, Juan Carlos; Vogt, Richard C.; Ávila, Robson W.; Farias, Izeni Pires; Gordo, Marcelo; Hrbek, Tomas (Zootaxa, 2018)
The description of Amazophrynella minuta was published in 1941 by the Swedish naturalist Douglas Melin based on material from Taracuá (Amazonas state, Brazil). This description was very brief and based on the morphology of few specimens with diagnostic characters and color variation not well defined. Moreover, the type series is currently in poor state of conservation. Consequently, taxonomic ambiguity surrounds the nominal taxon A. minuta, which hampers the description of many unnamed congeneric species. Herein, we redescribe A. minuta based on recently collected specimens from the type locality, designate a lectotype, formulate a new diagnosis, provide patterns of morphological variation, measurements and body proportions.